Hohe Geschwindigkeitsüberschreitung erfordert Fahrverbot. - (:unkn) unknown (Beck, 2002)
OLG Hamm, Beschluss vom 24.10.2001 - 2 Ss OWi 916/01. difu
Keywords: Straßenverkehr; Individualverkehr; Verkehrssicherheit; Verkehrsgeschwindigkeit; Geschwindigkeitsüberschreitung; Fahrverbot; Autofahrer